Assesment the online training environmets. The case of DIPRO 2.0. - Verónica Marín Díaz; Julio Cabero Almenara; Julio Barroso-Osuna (Universitat Politècnica de València, 2014)
The appearance of Internet in the higher education agenda has become, day by day,  a  phenomenon  of  an  increasing relevance,  principally  by  the  tools that have been created from different perspectives in their support. Thus, the development of educational proposals, with 2.0 tools, aimed at higher education students  is  a  reality  today,  according with  the  demand  for  new  teaching methods in the implementation of the European Higher Education Area (EHEA). In this paper we present the results of the assessment that college students do about an online learning environment designed within a research project. We sought  to  determine  whether  these valuations are determined by variables such as sex, age or university where they pursue  their  studies.  The  participant sample corresponds to the students of the degrees of Bachelor in Elementary Education and Early Childhood Education at the Universities of Cordoba, Seville and the Basque Country. The main results are  referred  to  the  positive  attitude that college students have in relation to  proposals  for  online  learning  that support  their  self-regulated  learning. Significant differences according to the university where they studied were also found.